The impact of monetary policy on bank lending rate in South Africa - Tunde, Matemilola Bolaji; Amin Noordin, Bany Ariffin; Etudaiye-Muhtar, Oyebola Fatima (Borsa Istanbul Anonim Sirketi, 2015)
The pass-through of the policy rates to bank lending rate is an important subject matter because it measures the effectiveness of monetary policy to control inflation or stabilize the economy. This study investigates the long-run interest rate pass-through of the money market rate to the bank lending rate and asymmetric adjustment of the bank lending rate. The study applies the momentum threshold autoregressive and asymmetric error correction models. The asymmetric error correction results reveal that bank lending rate adjusts to a decrease in the money market rate in South Africa. The findings suggest that the South African commercial banks adjust their lending rate downward but the lending rate appears rigid upward, which supports the customer reaction hypothesis.